Marketing Guidelines for Electrical Appliances of Chaiyaphan Future Mall Partnership Limited, Yasothon Province - Techasothon, Suphakrit; Patanathabutr, Ruchirat (Journal of Modern Learning Development, 2021)
The objectives of this research were 1) the components of electrical appliances marketing, and 2) to creating guidelines for electrical appliances marketing of Chaiyaphan Future Mall. This research was a mixed method research that used qualitative research and quantitative research. Sampling groups were 512 samples, whom 12 important keys in the electrical appliances marketing form purposive sampling, and 500 respondents whom the customers’ Chaiyaphan Future Mall form purposive sampling. The data were collected by interview and questionnaires. The statistics used were percentage and exploratory factor analysis. The following were the results: 1. the components of electrical appliances marketing for the customers’ Chaiyaphan Future Mall can classify 8 elements. There were 1) Core Products Value, (2) Unique Service and Promotions, (3) Satisfied Credit’s Terms, (4) Trusted Price, (5) Outstanding Messages, (6) Memorable Experiences, (7) Everyday Life Influencers, and (8) Reachable Functions. The components of electrical appliances marketing was “CUSTOMER”. 2. The a guideline of the Chaiyaphan Future Mall had 8 guidelines, 9 projects. That was guideline for further development, keep customers and increase sales of electrical appliances. In the year 2021 had total budget about 357,000 baht.